Alternative sanitizers to paraformaldehyde for incubation of fertile eggs - Gabriel da S. Oliveira; Vinícius M. dos Santos; Sheila T. Nascimento; Jullyana C. Rodrigues (Poultry Science, 2020)
The aim of this study was to evaluate an ethanolic extract of propolis and clove essential oil as a substitute for paraformaldehyde for the sanitation of fertile eggs. In total, 1,800 hatching eggs (from 40-week-old CPK [Pesadão Vermelho] breeder hens) were randomly distributed among the treatments (grain alcohol, clove essential oil, ethanolic extract of propolis, and paraformaldehyde). Spraying was the application method for all treatments except for paraformaldehyde, for which fumigation was used. The experimental design was a randomized block design with 4 treatments. Analysis of the incubation parameters was based on 6 replications per treatment. The egg weight loss was lower in the eggs treated with ethanolic extract of propolis (8.59 ± 3.34%) than in the eggs treated with grain alcohol (13.40 ± 2.87%), clove essential oil (12.96 ± 3.33%), and paraformaldehyde (13.05 ± 3.24%). The hatchability of the fertile eggs (51.39 ± 5.81%) and the hatchability of the set eggs (44.74 ± 6.79%) were negatively affected by the application of ethanolic extract of propolis. Late mortality of eggs treated was higher than early mortality in the grain alcohol (12.14 ± 4.72%; 2.86 ± 3.30%), clove essential oil (4.60 ± 5.95%; 3.03 ± 3.50%), and ethanolic extract of propolis (36.63 ± 6.60%, 11.98 ± 4.30%) treatments. The eggs treated with clove essential oil (67.90 ± 1.87%), paraformaldehyde (67.80 ± 1.85%), or grain alcohol (67.50 ± 1.92%) presented chick yields as expected. However, due to the high yield of eggs treated with ethanolic extract of propolis (69.25 ± 1.68%), its application at the concentration used in the present research is not recommended. Clove essential oil, when sprayed on fertile eggs as a sanitizing agent, did not differ from paraformaldehyde in relation to hatchery performance parameters.